Comparison between Spinoza's and Jewish philosophers notion of death - Souza, Nei Ricardo de (Cadernos Espinosanos, 2023)
The influences of the Jewish philosophy on Spinoza’s work have been recurrently researched, but no work has specifically addressed the issue of death. Te aim of this article, therefore, is to describe the conceptions of death in the Jewish philosophers read by Spinoza and to compare them with his notion of death. The method used consists of a bibliographic review of the main works of the authors considered here, Maimonides, Gersonides, Hasdai Crescas, Ibn Ezra and Ibn Gabirol, followed by a comparison with Spinoza. We conclude that Spinoza carried out a critical analysis of the ideas of these authors based on the logic of his propositions and presented a notion of death that is purified from Aristotelian references that were still present in Jewish philosophy.